Development of extruded animal feed based on fat and oil industry waste - Petik, I.; Петік, І.; Litvinenko, O.; Литвиненко, О.; Kalyna, Viktoriia; Калина, Вікторія Сергіївна; Ilinska, O.; Ільїнська, О.; Raiko, V.; Райко, В.; Filenko, O.; Філенко, О.; et al. (Український державний університет залізничного транспорту, 2023)
The paper considers the way to solve the problem of processing waste from the oil and fat industry, namely sunflower and soybean meals, which are a source of many valuable substances. The peculiarity of the work lies in determining the rational ratio of the base components of extruded animal feed, which is an important aspect of obtaining highquality competitive products. The research object is the use of oil and fat industry waste in extruded animal feed technology. The rational ratio of the components of extruded animal feed has been determined. The rational ratio of animal feed components is: sunflower meal – 0.40 parts by weight; soybean meal – 0.25 parts by weight; oatmeal – 0.35 parts by weight. The animal feed sample with justified composition corresponds to the commercial analogue in terms of porosity (72 % and 76 %, respectively) and cost ($285/t and $285/t, respectively). In addition, the extruded feed with the developed composition exceeds the commercial analogue in terms of protein content by 3.2 times and essential amino acids content by 2.9 times. The obtained data are explained by the use of a complex of components, namely oil and fat waste and starch-containing grain raw materials with various limiting amino acids and various technological features of the extruded mass of their mixture. The feature of the obtained results is the possibility to control the technological characteristic (porosity) of the finished product depending on the components ratio, which allows changing product characteristics according to consumer requirements. The research results make it possible to efficiently process secondary products of oilseed processing into a new competitive marketable product. From a practical point of view, the technology makes it possible to reduce the cost of storage/utilization of industry waste, get additional income from new products sales and improve environmental conditions. The applied aspect of using the scientific result is the possibility to create a range of animal feed with different technological indicators depending on the components ratio. Об’єктом дослідження є застосування відходів олієжирових виробництв в технології екструдованого корму для тварин. Встановлено раціональне співвідношення складових екструдованого корму для тварин. Раціональне співвідношення складових корму для тварин становить: соняшниковий шрот – 0,40 мас. частки; соєвий шрот – 0,25 мас. частки; вівсяна крупа – 0,35 мас. частки. Зразок корму для тварин обґрунтованого складу відповідає показникам комерційного аналогу за величиною пористості (72 і 76 % відповідно) та за вартістю (285 і 273 дол. США/т відповідно). Крім того, екструдований корм розробленого складу перевищує комерційний аналог за вмістом білку в 3,2 рази і за вмістом незамінних амінокислот в 2,9 разів. Отримані дані пояснюються тим, що використано комплекс складових – відходів олієжирової промисловості та крохмалевміної зернової сировини з різними лімітуючими амінокислотами та різними технологічними особливостями екструдованої маси їхньої суміші. Особливістю отриманих результатів є можливість регулювання технологічної характеристики готового продукту (пористості) в залежності від співвідношення компонентів, що дозволяє змінювати характеристики продукту згідно вимог споживача. Результати досліджень дозволяють ефективно перероблювати вторинні продукти переробки олійного насіння в новий конкурентоспроможній товарний продукт. З практичної точки зору технологія дозволяє знизити витрати на зберігання/утилізацію відходів виробництва, одержати додатковий дохід з реалізації нової продукції, а також покращити екологічний стан навколишнього середовища. Прикладним аспектом використання наукового результату є можливість створення асортименту кормів для тварин з різними технологічними показниками в залежності від співвідношення складових.
Використання відходів олієжирових виробництв як сировини для екструдованого корму для тварин
Keywords: extruded feed; екструдований корм; sunflower meal; соняшниковий шрот; soybean meal; соєвий шрот; oatmeal; вівсяна крупа; amino acid score; амінокислотна оцінка; technological indicators; технологічні показники